Population-based genomic study of Plasmodium vivax malaria in seven Brazilian states and across South America (2023)
ABSTRACT: Background Brazil is a unique and understudied setting for malaria, with complex foci of transmission associated with human and environmental conditions. An understanding of the population genomic diversity of P. vivax parasites across Brazil can support malaria control strategies. Methods Through whole genome sequencing of P. vivax isolates across 7 Brazilian states, we use population genomic approaches to compare genetic diversity within country (n = 123), continent (6 countries, n = 315) and globally (26 countries, n = 885). Findings We confirm that South American isolates are distinct, have more ancestral populations than the other global regions, with differentiating mutations in genes under selective pressure linked to antimalarial drugs (pvmdr1, pvdhfr-ts) and mosquito vectors (pvcrmp3, pvP45/48, pvP47). We demonstrate Brazil as a distinct parasite population, with signals of selection including ABC transporter (PvABCI3) and PHIST exported proteins. Interpretation Brazil has a complex population structure, with evidence of P. simium infections and Amazonian parasites separating into multiple clusters. Overall, our work provides the first Brazil-wide analysis of P. vivax population structure and identifies important mutations, which can inform future research and control measures.